Self-assembled microspheres composed of porous ZnO/CoO nanosheets for aqueous hybrid supercapacitors. (27th September 2019) - Zhou, Hongyan; Fu, Wenbin; Muhammad, Mir; Xie, Mingzheng; Xie, Erqing; Han, Weihua
Abstract: Hybrid supercapacitors (HSCs) are attractive in the field of energy storage systems, which can offer higher energy density than capacitors and higher power density than batteries. However, the battery-type electrodes in HSCs often suffer from low rate capability and cycling performance due to their poor electrical conductivity. Here, we demonstrated a positive battery-type electrode by using self-assembled flower-like microspheres (MSs). The MSs were composed of porous ZnO/CoO nanosheets. Compared with pristine CoO and ZnO electrodes, the ZnO/CoO composite electrode shows enhanced electrochemical performance with high specific capacity as well as high rate capability. A high capacity of 85 mAh g −1 ( 681 F g −1 ) is achieved at a high current density of 20 A g −1 . Such a favorable performance can be attributed to the ZnO introduction, which improves the electrical conductivity of the electrode, and the porous structure with interconnected pores, which provides fast ion/electron transport. When assembled with activated carbon, the HSCs can deliver high energy density (23.8 Wh kg −1 ) and power density (1.3 kW kg −1 ).